2021
DOI: 10.1002/ese3.886
|View full text |Cite
|
Sign up to set email alerts
|

Progress in proton‐conducting oxides as electrolytes for low‐temperature solid oxide fuel cells: From materials to devices

Abstract: Among various types of alternative energy devices, solid oxide fuel cells (SOFCs) operating at low temperatures (300‐600°C) show the advantages for both stationary and mobile electricity production. Proton‐conducting oxides as electrolyte materials play a critical role in the low‐temperature SOFCs (LT‐SOFCs). This review summarizes progress in proton‐conducting solid oxide electrolytes for LT‐SOFCs from materials to devices, with emphases on (1) strategies that have been proposed to tune the structures and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
74
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(85 citation statements)
references
References 231 publications
0
74
0
Order By: Relevance
“…Decades of research have revealed that the best protonic ceramic oxide materials are ABO 3 structured perovskite oxides in which the A-sites are predominantly filled with alkaline earth metals or rare metals with relatively large ionic sizes such as Ca, Sr, Ba, and La, while the B-sites are dominated by smaller sized tetravalent elements such as Zr and Ce. [91][92][93][94] These materials are relatively stable and exhibit a high level of proton conductivity. Ba for instance, has a large ionic size and for this reason, it is an A-site dominant material, whereas Ce and Zr are B-site dominant cations, respectively.…”
Section: Electrolyte Materialsmentioning
confidence: 99%
“…Decades of research have revealed that the best protonic ceramic oxide materials are ABO 3 structured perovskite oxides in which the A-sites are predominantly filled with alkaline earth metals or rare metals with relatively large ionic sizes such as Ca, Sr, Ba, and La, while the B-sites are dominated by smaller sized tetravalent elements such as Zr and Ce. [91][92][93][94] These materials are relatively stable and exhibit a high level of proton conductivity. Ba for instance, has a large ionic size and for this reason, it is an A-site dominant material, whereas Ce and Zr are B-site dominant cations, respectively.…”
Section: Electrolyte Materialsmentioning
confidence: 99%
“…proton-conducting electrolytes for intermediate temperature (450-700 °C) protonconducting ceramic fuel cells (IT-PCFCs). [1][2][3][4][5][6][7] Fully understanding the proton transport mechanisms is vital for the improvement of proton conductivity. To form protonic defects, BaMO 3 is doped with trivalent elements to create oxygen vacancies.…”
mentioning
confidence: 99%
“…Protonic ceramic electrical cells (PCEC) have an increasing research activity and show greater abilities for high performances and reversibility [1][2][3]. The use of high-temperature proton conductors (HTPCs) in such a system decreases the operating temperature in the 400-600 • C range and promotes better durability of the cells [1,2,4].…”
Section: Introductionmentioning
confidence: 99%